Effects of a Low-dose Leuprorelin Long Protocol on the Ovarian Response and Cycle Outcome in IVF - Yu-Chiao Yi; Ming-Jer Chen; Hua-Fen Ku; Esther Shih-Chu Ho (Elsevier, 2004)
Objective: The purpose of our study was to examine the effectiveness of a low-dose leuprolide long protocol in an in vitro fertilization (IVF) program. Materials and Methods: This was a retrospective analysis of the Department of Obstetrics and Gynecology IVF database at Taichung Veterans General Hospital, where the records for all patients who had received the long protocol beginning with a gonadotropin-releasing hormone agonist (GnRH-a) in the mid-luteal phase or gonadotropins alone between January 1, 1996, and December 31, 1998, were reviewed. Results: Patients received the low-dose GnRH-a protocol in 48 cycles (group 1), the standard-dose GnRH-a protocol in 37 cycles (group 2), and the gonadotropin-alone protocol in 96 cycles (group 3). There were no significant differences in terms of age, causes of infertility, or duration of infertility among the three groups. However, more patients in group 1 suffered from primary infertility. Responses to ovarian stimulation indicated that patients in both groups 1 and 2 required a higher gonadotropin dosage and a longer duration of stimulation compared with group 3. Group 1 patients had about the same preovulatory peak serum estradiol concentration and had similar numbers of retrieved oocytes compared to other patients, but required more stimulation days and higher total gonadotropin doses. Pregnancy rates were higher in both long-protocol groups (36.4%, 29.7%, and 22.9%, respectively), but differences did not reach statistical significance. There were also no significant differences in terms of abortion rates and multiple pregnancy rates. Furthermore, there was no spontaneous luteinizing hormone surge in group 1 or 2 patients. Conclusion: The low-dose GnRH-a down-regulation protocol can be considered an alternative to the standard- dose protocol. However, more studies are needed to find the optimal GnRH-a dose for clinical IVF.